The neuronal apoptosis inhibitory protein (NAIP) analysis of human and murine genetics. - Yaraghi, Zahra. (University of Ottawa (Canada), 1999)
The spinal muscular atrophies (SMAs), characterized by the degeneration of spinal cord motor neurons resulting in muscular atrophy, are among the most common autosomal recessive disorders. All forms of SMA map to chromosome 5 at 5q13. The interval containing the SMA gene was defined by linkage analysis and the identification of recombination events to an approximately 1.1 Mb region flanked centromerically by the DNA marker D5S629 and telomerically by the DNA marker D5S557. In the first part of this study I describe a recombination event on an SMA chromosome from a type I SMA family, occurring between different subloci of two complex microsatellite repeats (MSR), CMS-1 and 7613. This new proximal boundary reduced the minimal region harboring the SMA locus from ∼1.1 Mb to approximately 600 kb. It was within this newly defined SMA interval that an SMA associated gene, designated NAIP (Neuronal Apoptosis Inhibitory Protein), was cloned in 1995. NAIP exists in multiple copies in the SMA region at 5q13. Deletions in the first two coding exons of the only intact copy of NAIP are associated with approximately 66% of type I SMA cases and a lower percentage of the milder cases. The NAIP protein is homologous to the baculoviral inhibitor of apoptosis proteins, and is present in motor neurons and other neuronal populations affected in type I SMA. In the second part of this study I report the cloning and characterization of multiple copies of the mouse homologue of NAIP, all of which map to mouse chromosome 13, region D1-D3, which is syntenic to the human chromosome 5q11-q23. The analysis of the genomic organization of Naip indicated the existence of a minimum of six distinct Naip loci in the mouse. The original reason for the cloning of the mouse homologues of NAIP was to generate a knockout mouse model for SMA. Thus, as a first step toward this goal, I describe the targeted disruption of the CNS locus, Naip1, in ES cells. A report on the mapping of the multiple Naip loci to the critical region of Lgn1, a locus modulating the intracellular replication of Legionella in macrophages and therefore its pathogenicity, made Naip a candidate gene for murine Legionella resistance. Here I report further characterization of Naip2, as the locus most suited for this candidacy. Taken together, my data reveal that in contrast to the human case where there is one intact NAIP gene and multiple unprocessed truncated and deleted pseudogenes, the mouse possesses multiple potentially functional Naip loci representing a gene family. (Abstract shortened by UMI.)
Keywords: Biology, Molecular.